PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS SAINTIFIK PADA MATERI SISTEM PEREDARAN DARAH KELAS VIII SMP NEGERI 1 LAHUSA - Amazihono, Tuti Mariati (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research aims to produce scientifically based products on circulatory system materials that are valid, practical and effective. This type of research is the development of a 4-D Model, namely defining, designing, developing and disseminating. The research method used in this research is research and development. Based on the results of the development of scientific-based LKPD on the circulatory system material for class VIII SMP Negeri 1 Lahusa, it can be used by teachers and students in teaching and learning activities, showing very valid results. This can be seen from the results obtained, namely the results of the validator (Lecturer) test with an average score of 87.49%, the results of the practicality test by the teacher with a score of 4, stated to be very practical, the practicality test by students with an average 3.87, stated to be very practical, testing students' effectiveness during the learning process using LKPD was categorized as very effective, student motivation results with an average score of 94.59% in the very high category and student learning outcomes in the cognitive domain showed very good results with average 84.5. So, it can be concluded that the development of scientific-based LKPD on scientific-based circulatory system material is declared valid, practical and effective and can increase student motivation and learning outcomes. The suggestion in this research is that science subject teachers should be able to use learning LKPD as teaching materials in the teaching and learning process because it can simplify the teaching and learning process activities and can increase student motivation and learning outcomes.